IMPLICATURE IN TOGO’S MOVIE SCRIPT - Grace Yohana Gultom; Charles David Marudut Silalahi; Aish Manisha (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the use of implicature in the script of the movie Togo, focusing on how implied meanings are conveyed through dialogue and contextual cues. Implicature, a concept rooted in pragmatics, plays a crucial role in shaping character interactions, advancing the plot, and enriching the narrative without explicit statements. By analyzing selected scenes from the movie, this research identifies the types of implicature employed, such as conversational and conventional implicatures, and explores their functions in enhancing emotional depth, humor, and thematic resonance. The findings highlight the significance of implicature in cinematic storytelling, demonstrating how it contributes to audience engagement and interpretation. This study not only sheds light on the linguistic strategies used in Togo but also offers insights into the broader application of implicature in film scripts.